The concept of amal jama’i according to the Prophet’s tradition: an overview - Abdul Rahman, Mohd Nizho; Azhar, Alias (Perpustakaan IAIN Antasari Lt. 1, 2015)
This paper focuses on Islamic management issues as one of excellent legacies left by the Prophet (S.A.W). This paper will review the accomplishment of Islamic approach to management which had been practiced by the Prophet SAW and his companions.Based on archival research method, this paper will analyze the concept of Amal Jama’i(team work) based on Islamic management centered on the traditions of the Prophet (SAW). The discussion showed that team work is an imperative element in Islamic management and not merely confined to the practice of da’wah (inviting to Islam) but also in term of daily activities. In fact, the practice had been taught and shown by the Prophet (SAW).Even though the West had introduced many contemporary management theories, there is a huge difference compared to the Islamic approach to management.The concept of management in Islam does not merely based on material gained but also spiritual attainment and heavily emphasizes on the equality of the spiritual and material